Χρήση προϊόντων ζύμης στην διατροφή μηρυκαστικών - Αντωνίου, Κυριακή (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This review study explores the role of yeast products use in the diet of ruminants. The central issue was to study the role and effect of using yeast products in feed in relation to rumen environment, microbial activity as well as animal health and production. The effect of yeast products on the quality and quantity of milk of cow and small ruminants was also studied.
Keywords: Yeast products; Diet; Ruminants; Προϊόντα ζύμης; Διατροφή; Μηρυκαστικά